HUBUNGAN TINGKAT PENGETAHUAN DAN STATUS GIZI DENGAN ASUPAN CAIRAN PADA REMAJA DI SMK YARSI MEDIKA - Elvina; Rina Puspita Sari; Ahmad Yunus Gunawan Wibisono (Nusantara Hasana Berdikari, 2022)
Fluid intake in adolescents is very necessary during the stages of growth and development to maintain body fluid balance. Factors that can affect fluid intake in adolescents are the level of knowledge about fluid intake and nutritional status from the value BMI/Age. Research purposes to identify the Relationship Level of Knowledge and Nutritional Status with Fluid Intake at SMK Yarsi Medika. Research Methods: This study uses a descriptive quantitative correlation method. Sampling was done by using a total sampling technique based on data SMK Yarsi Medika. Research Results: The data analysis technique used is Chi-Square Test get the results of P-Value = 0,000 < 0,05. Conclusion: There is a between Relationship Level of Knowledge and Nutritional Status with Fluid Intake at SMK Yarsi Medika. Suggestion: Expected the adolescents can maintain adequate fluid intake in a day.